Ratiometric Photoacoustic Molecular Imaging for Methylmercury Detection in Living Subjects - Liu, Yi; Wang, Sheng; Ma, Ying; Lin, Jing; Wang, Hai‐Yan; Gu, Yueqing; Chen, Xiaoyuan; Huang, Peng (Advanced materials (Weinheim), 2017)
Photoacoustic molecular imaging is an emerging and promising diagnostic tool for heavy metal ions detection. Methylmercury (MeHg+) is one of the most potent neurotoxins, which damages the brain and nervous system of human beings through fish consumption. The development of a selective and sensitive method for MeHg+ detection is highly desirable. In this Communication, we develope a chemoselective photoacoustic sensor (LP‐hCy7) composed of the liposome (LP) and MeHg+‐responsive near‐infrared (NIR) cyanine dye (hCy7) for MeHg+ detection within living subjects, such as zebrafish and mouse. The as‐prepared LP‐hCy7 nanoprobe displays unique dual‐shift NIR absorbance peaks and produces a normalized turn‐on response after the reaction of MeHg+ and hCy7 through a mercury‐promoted cyclization reaction. The absorbance intensities of LP‐hCy7 nanoprobe at 690 and 860 nm are decreased and increased, respectively. The ratiometric photoacoustic signal (PA860/PA690) is noticeably increased in the presence of MeHg+. These findings not only provide a ratiometric photoacoustic molecular imaging probe for the detection of metal ions in vivo, but also provides a tool for spectroscopic photoacoustic molecular imaging. A promising MeHg+ (methylmercury) detection strategy by ratiometric photoacoustic molecular imaging shows very high sensitivity and selectivity in living subjects, such as zebrafish and mouse. MeHg+ is one of the most potent neurotoxins and can damage the brain and nervous system of human beings through fish consumption. Therefore, the development of this visualization tool is highly desirable.